2015
DOI: 10.1186/s12863-015-0279-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of CD40 polymorphisms with CD40 serum levels and risk of systemic lupus erythematosus

Abstract: BackgroundCurrent evidence shows that the CD40–CD40 ligand (CD40–CD40L) system plays a crucial role in the development, progression and outcome of systemic lupus erythematosus (SLE). The aim of this study was to investigate whether a CD40 gene single nucleotide polymorphism (SNP) is associated with SLE and CD40 expression in the Chinese population. We included controls (n = 220) and patients with either SLE (n =205) in the study.MethodsThe gene polymorphism was measured using Snapshot SNP genotyping assays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
7
30
1
1
Order By: Relevance
“…For instance, Field et al (2015) found the minor T allele to be associated with reduced CD40 expression in APCs, related to an increased proportion of the short mRNA isoform encoding the secreted form of CD40. This is consistent with the work of Chen et al (2015), who observed elevated levels of soluble CD40 in SLE patients carrying the T allele. On the other hand, Jacobson et al (2005) showed that the rs1883832 SNP does not affect transcription, but can influence translation efficiency.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For instance, Field et al (2015) found the minor T allele to be associated with reduced CD40 expression in APCs, related to an increased proportion of the short mRNA isoform encoding the secreted form of CD40. This is consistent with the work of Chen et al (2015), who observed elevated levels of soluble CD40 in SLE patients carrying the T allele. On the other hand, Jacobson et al (2005) showed that the rs1883832 SNP does not affect transcription, but can influence translation efficiency.…”
Section: Discussionsupporting
confidence: 93%
“…The CD40 SNPs rs1883832 and rs4810485 have been identified as susceptibility markers for this and other autoimmune diseases, such as GD (Tomer et al, 2002;Kim et al, 2003;Li et al, 2012), MS (Blanco-Kelly et al, 2010;Sokolova et al, 2013), and SLE (Vazgiourakis et al, 2011;Chen et al, 2015;Lee et al, 2015). In addition, several studies suggest that these polymorphisms affect CD40 expression at the mRNA and protein level (Jacobson et al, 2005;Vazgiourakis et al, 2011;Field et al, 2015;Wagner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, B cells lacking A20 had an increase response to activation with different stimuli, including anti-CD40 (43). Polymorphisms in the CD40 locus in Chinese, Turkish, and Greek populations have been linked to SLE (44,45), but it is unknown if these SNPs confer any altered risk of SLE to African American individuals. In fact, we could not find any evidence in our cohort of an intrinsic propensity of B cells from African American patients to respond differently to CD40L stimulation.…”
Section: Discussionmentioning
confidence: 99%